Adult Mosquito Fauna of Kura-Aras Basin - Berna Demirci (Türkiye Parazitoloji Dergisi, 2021)

(untitled)
Objective:To identify the adult mosquito species of Kura-Aras Basin, which includes Kars-Ardahan Plateau and Aras Valley, mosquito sampling was done in August and September 2020.Methods:Adult mosquitoes were collected using new Jersey light traps and mouth aspirators.Results:A total of 5.361 adult mosquito species belonging to five genera (Aedes caspius, Aedes vexans, Anopheles hyrcanus, Anopheles maculipennis s.l., Anopheles superpictus, Culex hortensis, Culex theileri, Culex pipiens s.l., Coquillettidia richiardii, Culiseta annulata, Culiseta longiearolata and Culiseta subochera) were sampled.Conclusion:Species detected in the study area are important vectors for public health, since they carry pathogens, such as malaria, West Nile virus, and various nematodes. These species can be used for arbovirus and malaria research studies.